Effects of rhythmic auditory guide on sprint running - Shinnosuke Hase; Kento Nakagawa; Shigeo Iso (PLoS ONE, 2025)
Auditory guides can influence the tempo of rhythmic movements, potentially enhancing running performance by improving parameters. Many previous studies have focused on low-speed running, but there is a lack of research on high-speed sprint running. This study investigated whether a metronome-based rhythmic auditory guide could modulate sprint running motions. Twenty-two junior high school students participated in the study, performing three 40-meter sprint trials under different conditions: (1) without an auditory guide (baseline), (2) with a slow-rhythm auditory guide (3.40 ±  0.24 Hz), and (3) with a fast-rhythm auditory guide (4.16 ±  0.29 Hz). Step rate, step length, and sprint velocity were analyzed using video recordings. The slow-rhythm auditory guide significantly decreased the step rate and increased the step length compared with the baseline condition (p <  0.05). Conversely, the fast-rhythm auditory guide significantly increased step rate and decreased step length (p <  0.05). These findings demonstrate that rhythmic auditory guides can effectively alter step rate and step length during sprint running in junior high school athletes. This suggests that auditory stimulus training could be a useful tool for coaching.